Feasibility and acceptability of HIV screening through the use of rapid tests by general practitioners in a Brussels area with a substantial African community. (28th August 2013) - Gennotte, A‐F; Semaille, P; Ellis, C; Necsoi, C; Abdulatif, M; Chellum, N; Evaldre, C; Laporte, F; Mernier, M; Ounchif, K; Gidiuta, D; Schellens, M‐J; et al.
Abstract : Objectives: To assess:1) if HIV screening with rapid tests in neighbourhoods with a substantial African community is feasible and acceptable among GPs and patients; 2) HIV seroprevalence. Methods: Multicenter prospective study with 10 trained physicians. Use of HIV standard test and INSTI Ultrarapid test. Inclusion criteria: MSM, sex worker, multiple sexual partners, having returned or coming from a country with high HIV prevalence, IVDU, Indicator conditions as defined by HIV Indicator Diseases across Europe Study, having an AIDS‐defining illness, having had a recent pregnancy or abortion; or presenting other risks. Results: From August 2010 to August 2011, 10 trained GPs offered an HIV test to 224 patients: 51% ♀, 48% ♂, 43% Caucasians, 45% Africans. Inclusion criteria: 32% "high risk group", 9% returning from an endemic country, 29% with an indicator condition; 12 patients (6%) refused the standard test. The INSTI was offered to 217(97%), 197 performed with 2 reactive rapid tests confirmed. The seroprevalence according to ethnic origin was 0% among Caucasians and 2.2% among Africans and was 1.5% among patients with an indicator condition. 1087 consecutive consultations of the same GPs were recorded: 42% patients had ≥1 inclusion criteria among which 41% of offered tests, that is to say 59% of "missed opportunities". The reasons for not offering the test as recorded for 55% of patients:"not indicated" 44.5%, "no time" 33%, "impossible to propose" 15%, test completed previously 11%, known HIV‐positive 4%. Conclusions: Standard and rapid tests are well received by patients but were usually not offered by doctors who have been trained.